An overview of hereditary spherocytosis and the curative effects of splenectomy - Turpaev, Kyril; Bovt, Elizaveta; Shakhidzhanov, Soslan; Sinauridze, Elena; Smetanina, Nataliya; Koleva, Larisa; Kushnir, Nikita; Suvorova, Anna; Ataullakhanov, Fazoil (Frontiers in Physiology, 2025)
Hereditary spherocytosis is a common hemolytic anemia with different severity. The causes of hereditary spherocytosis are mutations in genes that encode red blood cell (RBC) membrane and cytoskeletal proteins, including ankyrin-1, Band 3 (or AE1), α spectrin, β spectrin, and protein 4.2. Molecular defects in these proteins decrease membrane integrity, leading to vesiculation, decreased membrane surface area, and reduced deformability of the cells. Eventually, this leads to the trapping the abnormal RBCs (spherocytes) in the spleen. In most severe cases, splenectomy may be necessary to prevent general RBC collapse during the passage of RBCs through the narrow slits of venous sinuses in the spleen. The clinical benefit of splenectomy results from elimination the primary site of RBC damage and destruction. Splenectomy is a curative approach but can cause complications and should be undertaken after examination by various laboratory approaches. Splenectomy does not correct most genetically determined membrane abnormalities in erythrocytes in patients with hereditary spherocytosis. The transformation of biconcave erythrocytes into spherocytes continues, although to a lesser degree than before surgery. Nevertheless, splenectomy increases the lifespan of red cells, significantly reducing the severity of anemia and improving many physiological signs of HS.